2017
DOI: 10.1371/journal.pone.0169204
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Radioresistant Prostate Cancer Cells by Resveratrol Isolated from Arachis hypogaea Stems

Abstract: Resveratrol (RV, 3,4ʹ,5-trihydroxystilbene) is naturally produced by a wide variety of plants including grapes and peanuts (Arachis hypogaea). However, the yield of RV from peanut stem and its potential radiosensitizing effects in prostate cancer (PCa) have not been well investigated. In this study, we characterized RV in peanut stem extract (PSE) for the first time and showed that both RV and PSE dose-dependently induced cell death in DOC-2/DAB2 interactive protein (DAB2IP)-deficient PCa cells with the radior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 52 publications
(60 reference statements)
5
16
0
Order By: Relevance
“…While further studies are required to understand the underlying mechanisms, these differential effects could be related to a possible drug interaction or synergistic effect on bone tissue with the combination treatment of resveratrol and MTX. This is also consistent with a recent study which showed a synergistic effect of resveratrol combined with radiation in killing the radioresistant prostate cancers in vitro and in enhancing radiation therapy of the mouse model of prostate cancer cell xenograft tumour [39]. Furthermore, our observations of the harmful effect at 10 mg/kg and yet the protective effect on bone at 1 mg/kg of resveratrol in this MTX chemotherapy setting support the view of the dose-dependency of resveratrol in its health benefits.…”
Section: Discussionsupporting
confidence: 93%
“…While further studies are required to understand the underlying mechanisms, these differential effects could be related to a possible drug interaction or synergistic effect on bone tissue with the combination treatment of resveratrol and MTX. This is also consistent with a recent study which showed a synergistic effect of resveratrol combined with radiation in killing the radioresistant prostate cancers in vitro and in enhancing radiation therapy of the mouse model of prostate cancer cell xenograft tumour [39]. Furthermore, our observations of the harmful effect at 10 mg/kg and yet the protective effect on bone at 1 mg/kg of resveratrol in this MTX chemotherapy setting support the view of the dose-dependency of resveratrol in its health benefits.…”
Section: Discussionsupporting
confidence: 93%
“…The differential concentration effects could be related to a possible drug interaction (between resveratrol and MTX) on bone tissue. Consistent with this, a recent study showed a synergistic effect of resveratrol and radiation treatment in killing radiation‐resistant prostate cancer cells and in treating prostate cancer cell xenograft tumors in mice . Furthermore, the observation of a harmful effect of resveratrol at 10 mg/kg (yet a protective effect at 1 mg/kg) on bone of MTX‐treated rats supports the proposed dose dependency of resveratrol health benefits .…”
Section: Potential Strategies For Preventing Methotrexate‐induced Bonsupporting
confidence: 68%
“…The number of surviving colonies were counted for evaluation of cell viability. Dose-survival curves for each experiment were constructed by plotting the mean SFs semi-logarithmically as a function of IR dose ( Chen et al, 2017 ). The data were analyzed and survival curves were plotted following the linear quadratic (LQ) model using GraphPad Prism 6.0 software (GraphPad Software, United States).…”
Section: Methodsmentioning
confidence: 99%